Cooperação e multi-level governance: o caso do Grande Recife Consórcio de Transporte Metropolitano - Best, Nina Juliette (2011)
The first Brazilian metropolitan regions were instituted in a top-down approach as part of a national development strategy during the military regime. Perceived as an undemocratic institution and rejected as a fou rth tier of government, these regions have, since the 1988 Constitution, been gradually emptied of their original purposes. In their orphanhood, socioeconomic problems have proliferated and deepened, and competitive rather than cooperative intergovernmental relations have predominated. One of the main challenges faced by the Brazilian federal model, in particular when referring to metropolitan regions, concerns the need for greater cooperation and coordination, necessary in order to ensure a more balanced relationship within the federation, as well as the effective implementation of policies to address inequality and social exclusion in these urban agglomerations. This article analyzes the Grande Recife Metropolitan Transport Consortium, established in 2008 between the governments of the Recife metropolitan region, in order to plan, manage and implement the public transport system in the region. The Grande Recife became a reality with the promulgation of a new instrument for federal cooperation, the Public Consortia Law in 2005. It is a pioneer and innovative experience that demonstrates it is possible to overcome conflicts and common challenges while simultaneously preserving autonomy and the rights of the citizens. The Grande Recife consortium is an experience in intergovernmental cooperation and an example of multi-level governance (MLG), illustrating a new democratic institutional arrangement between different governmental spheres for the shared management of a public service.